2016
DOI: 10.1038/srep21748
|View full text |Cite
|
Sign up to set email alerts
|

Relation between detection rate and inappropriate shocks in single versus dual chamber cardioverter-defibrillator – an analysis from the OPTION trial

Abstract: The programming of implantable cardioverter-defibrillators (ICDs) influences inappropriate shock rates. The aim of the study is to analyse rates of patients with appropriate and inappropriate shocks according to detection zones in the OPTION trial. All patients received dual chamber (DC) ICDs randomly assigned to be programmed either to single chamber (SC) or to DC settings including PARAD+ algorithm. In a post-hoc analysis, rates of patients with inappropriate and appropriate shocks were calculated for shocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
2
1
1
1
Order By: Relevance
“…However, in our cohort there was no significant difference in inappropriate shock rates in those with single or two-therapy zones programmed (p=1.00). The inappropriate shock rates in those with single treatment zone programming were similar to that of already published data (27,28). When excluding, from the TV-ICD group those with inappropriate shocks and two-therapy zone programming, the device-related complications were still significantly higher in the TV-ICD group compared to the S-ICD group (p=0.021).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, in our cohort there was no significant difference in inappropriate shock rates in those with single or two-therapy zones programmed (p=1.00). The inappropriate shock rates in those with single treatment zone programming were similar to that of already published data (27,28). When excluding, from the TV-ICD group those with inappropriate shocks and two-therapy zone programming, the device-related complications were still significantly higher in the TV-ICD group compared to the S-ICD group (p=0.021).…”
Section: Discussionsupporting
confidence: 86%
“…In all cases of inappropriate shocks we were able to prevent any further recurrence through altering the sensing vector. It has been shown that patients with TV-ICDs with two therapy zones programmed experience higher rates of inappropriate shocks (26)(27)(28). However, in our cohort there was no significant difference in inappropriate shock rates in those with single or two-therapy zones programmed (p=1.00).…”
Section: Discussioncontrasting
confidence: 65%
“…As the PARAD+® algorithm had been used as default tachyarrhythmia detection algorithm in the presence of a functional atrial lead, CARAT confirms results of previous studies such as OPTION 3 , 4 or ISIS-ICD 5 in terms of arrhythmia discrimination in dual-chamber devices. The present study also reports low inappropriate shocks in single-chamber devices, where arrhythmia discrimination is based on a combination of stability, acceleration, and ‘long cycle gap’ to identify atrial fibrillation.…”
Section: Discussionsupporting
confidence: 77%
“…Most of the randomized controlled trials and the pooled meta-analyses failed to show any superiority of dual-chamber ICD over single-chamber ICD for primary prevention. 101 , 102 , 103 , 104 The rates of inappropriate shock, hospitalization, or survival were similar. Therefore, a single-chamber ICD should be generally preferred over dual-chamber ICDs unless pacing is needed.…”
Section: Device Selection and Programmingmentioning
confidence: 89%